Alternative Approach toward the Aging of Asphalt Binder. Issue 1 (January 2015) - Hofko, Bernhard; Handle, Florian; Eberhardsteiner, Lukas; Hospodka, Markus; Blab, Ronald; Füssl, Josef; Grothe, Hinrich
Awareness that natural, financial, and energy resources are scarce goods has increased. Thus demand is growing for infrastructure that is not only of high quality but also efficient. Efficiency, in this case, aims to optimize cost and energy consumption over the complete life cycle of a structure. The objective is to build long-lasting infrastructure with low maintenance demands and with high recycling potential after it has reached the end of its service life. For bituminous bound materials, the aging of asphalt binder has a crucial impact on durability and recyclability. Because asphalt binder is organic by nature, the thermal and oxidative aging processes affected by chemical and structural changes occur when asphalt mixes first are produced and applied and continue over the course of their service life. Increasing stiffness and brittleness of the binder make pavement more prone to thermal and fatigue cracking. The interdisciplinary research project reported here worked toward a better understanding of the physicochemical fundamentals of asphalt binder aging, as well as of the impact of binder aging on the mechanical properties of asphalt binder and asphalt mixes. Through extensive chemical and mechanical analyses, a new model was developed to explain the aging process comprehensively (i.e., on the physicochemical and mechanical levels). Aging can be determined mathematically by micromechanical modeling. With the model presented in this paper, changes in asphalt binder as a result of aging (i.e., increasing brittleness and stiffness) can be explained.